Hydraulic system for wireless control of high clearance inter-row weeding in organic-product - Suleiman, Samaila; Wan Ismail, Wan Ishak; Mohd Kassim, Muhamad Saufi; Mahadi @ Othman, Muhammad Razif (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Pedestrian tractor or Power tiller is an essential machine for horticulture in many parts of the world. They are mainly used for tilling, ploughing and ground preparation in small agricultural fields. Many custom designs of implement/machines are used on the pedestrian tractor such as seeders, cultivators/weeder and levelers. However, operating these machines is extremely tedious, fatiguing and time consuming. Thus, introducing automation on the high clearance pedestrian weeder can reduce fatigue associated to its operation. This article presents a high clearance inter-row weeder aimed at weeding at various stages of crop height, thus producing organic product. The system also enabled flexible power transmission and remote monitoring of the machine through the 12V solenoid operated valves.